Ultraviolet exposure in the Ironman triathlon - Moehrle, M. (Medicine & Science in Sports & Exercise, 2001)
PURPOSE: Skin cancer is increasing worldwide and exposure to ultraviolet (UV) radiation is thought to be the most important environmental risk factor. People practicing outdoor sports are exposed to considerable amounts of UV radiation from the sun. METHODS: Three triathletes participated in the Ironman Triathlon World Championships 1999 in Hawaii (3.9-km swim, 180.2-km bike, 42.4-km run). They attached Bacillus subtilis spore film dosimeters (VioSpor) on the back between their shoulders. The dosimeter system measured cumulative biologically weighted erythemal UV exposure. UV exposure is given in minimal erythema doses (1 MED corresponds to 250 J.m-2 at 298 nm). RESULTS: The mean personal UV exposure was 8.3 MED (6.9-9.7 MED) after 8:43 to 9:44 h of competition corresponding to 0.8 to 1.3 MED.h-1 (bike and run). The athletes were sunburned despite the use of water-resistant sunscreen (SPF 25+) on sun exposed skin. CONCLUSION: The International Radiation Protection Agency has issued guidelines for professional UV exposure. Ironman triathletes considerably exceeded these limits of exposure similar to other outdoor sports. Professional and amateur athletes should be aware of hazards caused by UV radiation. Adequate protection by water-resistant sunscreens and clothing as well as training and competition schedules with low sun exposure seem to be a reasonable recommendation.